Xenophobic violence and the ambivalence of citizenship in post-apartheid South Africa. Issue 2 (17th February 2019) - Solomon, Ryan
ABSTRACT: This essay examines the way that the language of rights has been used to both justify and challenge xenophobia in South Africa. South Africa has struggled with incidents of xenophobic violence against African migrants, with major outbreaks of violence taking place in 2008 and in 2015, and despite substantial anti-xenophobia efforts, African migrants continue to be subject to discrimination and abuse. Part of the reason for the persistence of anti-African migrant sentiment is a prevailing rhetoric of victimization, which frames irregular African migrants as a threat to the rights of South Africa's poor. This essay analyzes that rhetoric, as well as analyzing how a grassroots movement of shackdwellers, Abhlali baseMjondolo, has challenged that rhetoric by highlighting the interconnection between the rights of citizens and noncitizens in the country. In examining the contestation over rights in South Africa, this essay seeks to engage with the ambivalence of citizenship in South Africa and the conflict between the human rights framework that has been established in the country and the necessary limitation of the rights of noncitizens.